IDENTIFIKASI TELUR CACING NEMATODA YANG TERDAPAT PADA SAYURAN SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN PADA KONSEP INVERTEBRATA KELAS NEMATODA DI SMA - Lestia Pratiwi; Suwondo '; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The aim of reseach was to determine of the eggs of various types of parasitic nematode worms found in vegetables and the results of this study is designed as an alternative medium of learning in the classroom invertebrates concept nematodes in February and May 2015. The study was conducted with two stages, namely the identification of various types of nematode eggs using a survey method and designing alternative learning media. Sampling was done by purposive sampling. The parameters observed in this study are various types of nematode worm eggs rich in vegetable lettuce (Lactuca sativa), basil (Ocimum basilicum L) and cabbage (Brassica oleracea). The results showed that nematode worm eggs found in vegetables lettuce (Lactuca sativa) is Trichuris trichiura and Necator americanus, basil (Ocimum basilicum L) was found on the eggs Ancylostoma duodenale and cabbage (Brassica oleracea) found eggs of Ascaris lumbricoides. Results of the study can be used as an alternative medium of learning in the form of video footage on the material invertebrates nematodes class in high school.Keywords: Nematode worm eggs, Lettuce (Lactuca sativa), Basil (Ocimum basilicum L), Cabbage (Brassica oleracea), Alternative Learning Media..